2021
DOI: 10.1111/jpy.13202
|View full text |Cite
|
Sign up to set email alerts
|

Type specimen sequencing, multilocus analyses, and species delimitation methods recognize the cosmopolitan Corallina berteroi and establish the northern Japanese C. yendoi sp. nov. (Corallinaceae, Rhodophyta)

Abstract: A partial rbcL sequence of the lectotype specimen of Corallina berteroi shows that it is the earliest available name for C. ferreyrae. Multilocus species delimitation analyses (ABGD, SPN, GMYC, bPTP, and BPP) using independent or concatenated COI, psbA, and rbcL sequences recognized one, two, or three species in this complex, but only with weak support for each species hypothesis. Conservatively, we recognize a single worldwide species in this complex of what appears to be multiple, evolving populations. Inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 81 publications
1
11
1
Order By: Relevance
“…Haplotype networks confirmed long-distance dispersal within the cosmopolitan species (occurring in three realms), P. bartlettii , P. caerulescens , and P. capillacea ( Figure 4 ). This result contrasts with recent studies that have shown that many allegedly widespread red algal species are actually multiple cryptic species with narrow ranges ( Won et al, 2009 ; Díaz-Tapia et al, 2018 ; Gabrielson et al, 2018 ; Leliaert et al, 2018 ; but see Calderon et al, 2021 ). For P. bartlettii , there was a close relationship between individuals from Vietnam and Brazil (~17,000 km apart), indicating recent long-distance dispersal or introductions, though we cannot discern the source vs. sink.…”
Section: Discussioncontrasting
confidence: 92%
“…Haplotype networks confirmed long-distance dispersal within the cosmopolitan species (occurring in three realms), P. bartlettii , P. caerulescens , and P. capillacea ( Figure 4 ). This result contrasts with recent studies that have shown that many allegedly widespread red algal species are actually multiple cryptic species with narrow ranges ( Won et al, 2009 ; Díaz-Tapia et al, 2018 ; Gabrielson et al, 2018 ; Leliaert et al, 2018 ; but see Calderon et al, 2021 ). For P. bartlettii , there was a close relationship between individuals from Vietnam and Brazil (~17,000 km apart), indicating recent long-distance dispersal or introductions, though we cannot discern the source vs. sink.…”
Section: Discussioncontrasting
confidence: 92%
“…4). However, based on length alone, specimens from the eastern Pacific could also be C. berteroi (Calderon et al 2021) or C. chilensis (Huber 2020), both with ranges overlapping that of C. vancouveriensis.…”
Section: Resultsmentioning
confidence: 99%
“…2015, Huber 2020, Calderon et al. 2021) and remains very useful for species delineation across crustose and geniculate coralline lineages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations